IDENTIFIKASI KERUSAKAN TANAMAN KOPI AKIBAT SERANGAN HAMA DI DESA SAMBIREJO KECAMATAN SELUPU REJANG KABUPATEN REJANG LEBONG - Sari, Venti Novita; Effendi, Darwan; Utami, Rizky Septika; Gustian, Meko; Ningrat, Bayu Cahya (Institute of Computer Science (IOCS), 2025)
One of the main challenges in maximizing the potential of coffee plantations is the low productivity and substandard quality that does not meet export requirements. The low productivity of coffee can be attributed to several factors, one of which is pest infestation. Identification of coffee insects is essential for effective pest management efforts and for breeders it is essential for early information in creating coffee plants that are resistant to insects. This study aims to identify the types of pests and assess the level of damage to coffee plants caused by pest attacks in coffee plantations located in Sambirejo Village, Selupu Rejang District, Rejang Lebong Regency. The research was conducted in December 2024 in the coffee plantations of Sambirejo Village. A qualitative descriptive approach was employed by collecting data through field observations and direct inspection of pests found on-site. The study was carried out at five different locations, with additional data gathered through interviews with local farmers. The findings revealed six pest species attacking coffee plants in the Sambirejo plantations: the mealybug (Pseudococcus lilacinus), green scale insect (Coccus viridis), black ants, stem borer (Zeuzera coffeae), coffee berry borer (Hypothenemus hampei), and grasshoppers (Xyronotidae). The extent of coffee plant damage due to pest attacks was categorized as follows: 72% light damage, 20% moderate damage, and 8% severe damage.